The effects of home energy efficiency upgrades on social housing tenants: Evidence from Ireland - Bryan Coyne; Sean Lyons; Daire McCoy (The Economic and Social Research Institute (ESRI), 2016)
This research examines the impact of a home energy efficiency upgrade programme on social housing tenants. Employing a quasi-experimental approach we examine a range of self-reported and objectively measured outcomes, including metered gas consumption, for a control and upgrade group, before and after the upgrade. We draw our sample from a large home energy efficiency programme in Ireland, The SEAI Better Energy Communities Scheme, which provides funding for whole communities to upgrade the efficiency of their dwellings. Dwellings are selected for upgrade based on need, allowing us to control for observable dwelling characteristics correlated with selection into the trial. The upgrades undertaken are extensive relative to the average home energy improvement in Ireland, with many dwellings receiving a number of measures, such as cavity wall, external wall and attic insulation; new boilers; replacement doors and windows; CFL lighting and heating controls. Households report improvements across a range of outcomes associated with heating-related deprivation and comfort in the home. Panel regression models examine the elasticity of gas demand with respect to the thermal efficiency of the dwellings. Overall, we find that use of natural gas falls much less than 1:1 for each increment to thermal efficiency of the home. For the average household in this study, about half of a marginal increase in thermal efficiency is reflected in reduced gas demand.
Keywords: H23; I38; Q40; Q52; 330; Energy efficiency upgrades; Social housing tenants; Ireland